2009
DOI: 10.1074/jbc.m109.022418
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3ζ Mediates Resistance of Diffuse Large B Cell Lymphoma to an Anthracycline-based Chemotherapeutic Regimen

Abstract: Patients presenting with diffuse large B cell lymphoma (DLBCL) are treated with a standard anthracycline-based chemotherapeutic mixture consisting of cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP). Half of DLBCL patients will develop chemo-refractory tumors due to the emergence of CHOP-resistant DLBCL cells. We isolated DLBCL cells that were resistant to CHOP as a model system to investigate the molecular basis of CHOP resistance. Resistant cells emerged from CHOP-sensitive DLBCL populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
22
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 47 publications
5
22
1
Order By: Relevance
“…Perhaps most importantly, our results showed that knocking down the expression of 14-3-3ζ in head and neck cancer cells enhanced the efficacy of CT. In support of our data, recent reports have shown similar results in lung cancer, breast cancer, gliomas, and B-cell lymphoma, independently suggesting a role of 14-3-3ζ in cell cycle progression and inhibition of apoptosis (18,33,34). Targeting 14-3-3ζ sensitized lung cancer cells to cisplatin treatment (33), and breast cancer cells (MCF7) to treatment with 5-FU and doxorubicin (19).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Perhaps most importantly, our results showed that knocking down the expression of 14-3-3ζ in head and neck cancer cells enhanced the efficacy of CT. In support of our data, recent reports have shown similar results in lung cancer, breast cancer, gliomas, and B-cell lymphoma, independently suggesting a role of 14-3-3ζ in cell cycle progression and inhibition of apoptosis (18,33,34). Targeting 14-3-3ζ sensitized lung cancer cells to cisplatin treatment (33), and breast cancer cells (MCF7) to treatment with 5-FU and doxorubicin (19).…”
Section: Discussionsupporting
confidence: 76%
“…Knocking down 14-3-3ζ expression sensitized chemorefractory diffuse B-cell lymphoma to an anthracycline-based chemotherapeutic cocktail consisting of cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP; ref. 34). Chatterjee et al (35) showed a novel role of 14-3-3ζ in mediating resistance of prostate cancer cells (DU-145) to topoisomerase I inhibitor, 9-nitrocamptothecin.…”
Section: Discussionmentioning
confidence: 99%
“…Although some of the other members of the 14-3-3 protein family, such as 14-3-3z and 14-3-3u/t, have been reported to also contribute to (Maxwell et al, 2009;Neal et al, 2009) and associate with (Hodgkinson et al, 2012) drug resistance, we did not find upregulation in expression of 14-3-3z and 14-3-3u/t in the gemcitabine-resistant G3K cells. This observation suggests that 14-3-3z and 14-3-3u/t may not participate in the acquired gemcitabine resistance in PDAC.…”
Section: Discussioncontrasting
confidence: 45%
“…14-3-3 (gene symbol YWHAZ) protects cells from numerous stresses, including chemotherapy-induced death, anoikis, and growth factor deprivation (2)(3)(4)(5)(6). Furthermore, 14-3-3 expression is upregulated in many cancers, and high-level expression has been shown to correlate with poor clinical outcomes in breast cancer (4,5,7,8).…”
mentioning
confidence: 99%